Post-pandemic online mathematics and statistics support: Practitioners’ opinions in Germany and Great Britain & Ireland - Gilbert, H.; Schürmann, M.; Liebendörfer, M.; Lawson, D.; Hodds, M. (International Journal of Mathematical Education in Science and Technology)
Keywords: Applied Mathematics; Education; Mathematics (miscellaneous)

Fachdidaktisches Design von Begründungsvideos im Projekt studiVEMINTvideos - Biehler, Rolf; Guntermann, Dominik; Liebendörfer, Michael; Krämer, Sandra; Schlüter, Sarah (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Erfassung und Vergleich (mathematischer) Eingangsvoraussetzungen angehender Studierender verschiedener mathematikhaltiger Studiengänge - Göller, Robin; Gildehaus, Lara; Liebendörfer, Michael; Besser, Michael (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2021. Beiträge zum gleichnamigen Online-Symposium am 12 November 2021 aus Bochum)

Zu digital - zu viel - zu schwer? Qualitative Einsichten in das Erleben und Handeln von Erstsemester-Studierenden der Mathematik während der Corona-Pandemie - Kempen, Leander; Liebendörfer, Michael (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2021. Beiträge zum gleichnamigen Online-Symposium am 12 November 2021 aus Bochum)

Bearbeitungsmuster von Studierenden im Umgang mit formalen Definitionen im Kontext konstanter Folgen - Schlüter, Sarah; Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Förderung prozeduraler Flexibilität durch Lernvideos mit interaktiven Aufgaben - Krämer, Sandra; Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Preservice teachers’ mathematics-related values and expectancy in the transition from school to university
Many preservice mathematics teachers lose their motivation during their first year at university. This phenomenon has been repeatedly described in recent years but is not yet fully understood. Since motivation may relate to different objects such as mathematics or teaching, we aim to qualitatively reconstruct different facets of the central motivational constructs of Situated-Expectancy-Value theory (intrinsic value, attainment value, utility value, cost, and expectancy of success) for preservice mathematics teachers. The analysis of longitudinal group interviews of 14 preservice higher-secondary mathematic teachers from a German university revealed different objects of motivation (e.g., teaching mathematics, scientific mathematics, procedural mathematics, or proof-based mathematics) in preservice teachers' values and expectancy of success. Furthermore, relations between those values and expectancy of success were identified that played a significant role in preservice teachers’ motivational development over their first semester (e.g., relations of attainment value for scientific mathematics and psychological cost). Theoretical and practical implications towards a teaching-specific conceptualization of expectancy of success and values and value interventions are being discussed.

Practice-Oriented Research in Tertiary Mathematics Education – An Introduction - Biehler, Rolf; Liebendörfer, Michael; Gueudet, Ghislaine; Rasmussen, Chris; Winsløw, Carl (Practice-Oriented Research in Tertiary Mathematics Education)

Framing Goals of Mathematics Support Measures - Liebendörfer, Michael; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Schürmann, Mirko; Biehler, Rolf; Schaper, Niclas (Practice-Oriented Research in Tertiary Mathematics Education)

Practice-Oriented Research in Tertiary Mathematics Education

Lernvideos und ihre Erstellung - Das Projekt studiVEMINTvideos - Biehler, Rolf; Liebendörfer, Michael; Schmitz, A. (Mitteilungen der Gesellschaft für Didaktik der Mathematik)

Fachdidaktisches Design von Begründungsvideos im Projekt studiVEMINTvideos - Biehler, Rolf; Guntermann, Dominik; Liebendörfer, Michael; Krämer, Sandra; Schlüter, Sarah (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

The role of learning strategies for performance in mathematics courses for engineers - Liebendörfer, Michael; Göller, Robin; Gildehaus, Lara; Kortemeyer, Jörg; Biehler, Rolf; Hochmuth, Reinhard; Ostsieker, Laura; Rode, Jana; Schaper, Niclas (International Journal of Mathematical Education in Science and Technology)
Keywords: Applied Mathematics; Education; Mathematics (miscellaneous)

Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse

Dokumentation der Erhebungsinstrumente des Projekts WiGeMath - Schürmann, Mirko; Büdenbender-Kuklinski, C.; Lankeit, Elisa; Liebendörfer, Michael; Hochmuth, R.; Biehler, Rolf; Schaper, N.

Einführung in das WiGeMath-Projekt: Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Hochmuth, Reinhard; Biehler, Rolf; Schaper, Niclas; Liebendörfer, Michael; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Ruge, Johanna; Schürmann, Mirko (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Ein Rahmenmodell für hochschuldidaktische Maßnahmen in der Mathematik - Liebendörfer, Michael; Hochmuth, Reinhard; Biehler, Rolf; Schaper, Niclas; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Ruge, Johanna; Schürmann, Mirko (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Evaluation von Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Schürmann, Mirko; Liebendörfer, Michael; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Ruge, Johanna; Schaper, Niclas; Biehler, Rolf; Hochmuth, Reinhard (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Enriching videos with interactive questions to enhance students’ cognitive activity: concept and implementation - Liebendörfer, Michael; Profeta, Angelo; Krämer, Sandra; Schlüter, Sarah; Becher, Silvia; Biehler, Rolf; Mai, Tobias; Schmitz, Angela

Consultation Phases in Mathematics Learning and Support Centres - Schürmann, Mirko; Panse, Anja; Shaikh, Zain; Biehler, Rolf; Schaper, Niclas; Liebendörfer, Michael; Hilgert, Joachim (International Journal of Research in Undergraduate Mathematics Education)
Abstract Mathematics Learning Support Centres are becoming more and more common in higher education both internationally and in Germany. Whereas it is clear that their quality largely depends on a functioning interaction in consultations, little is known about how such consultations proceed in detail. On the basis of models from the literature and recorded support sessions (N = 36), we constructed a process model that divides consultations into four ideal–typical phases. In the individual consultations, forward or backward leaps occur, but overall the model seems to describe the data well. A high intercoder reliability shows that it can be applied consistently on real data by different researchers. An analysis of the consultations between students and tutors shows that both mainly work on past attempts or thoughts of the students to solve the exercise or problems and on concrete strategies to solve a problem within the session. In contrast, very little time is dedicated to summarizing and reflecting the solution. The data allows for a more in-depth discussion of what constitutes quality in advising processes and how it might be further explored. Practically, the model may structure support sessions and help in focussing on different goals in different phases.
Keywords: Education; Mathematics (miscellaneous)